Arabic Language Learning (All) for kids - Salim, Trigui Mohamed; Zulkifli, Abdul Nasir; Faisal Mohamed, Nur Fadziana; Abd Razak, Abd Hadi; Saad, Mohd Nizam (2010)
Arabic Language has an exceptional position in Islam.It is the language of Quran, thus the need to learn and understand Arabic amongst Muslims is of paramount importance. For countries where their native language is not Arabic, the language is only taught in special schools. Arabic language needs to be introduced to children at early ages such as in the kindergarten.With the advent of computer technology, various kind of multimedia tools have been developed for the purpose of language learning.Since children are attracted to computer applications especially those that involve multimedia, there is a need to develop Arabic language learning applications for them.Even though there are few applications available in the market for that purpose, most of them do not fully utilize the multimedia elements.The prime objective of this study was to propose an Arabic Language Learning (ALL) for kids of ages between 4 to 6 years old that enable them to learn the language.In the process, an interactive field-tested ALL for kids has been developed as an alternative to the traditional learning tools.The results of user evaluation on the ALL indicate that it has good usability in terms of Learn ability, Usefulness, Ease of Use and Outcome/Future Use.The results also indicate that there is a significant difference between novice and expert users for Usefulness and Ease of Use, while no significant difference for learn ability and Outcome/Future Use.